2009
DOI: 10.1380/ejssnt.2009.513
|View full text |Cite
|
Sign up to set email alerts
|

Interface Structure of an Epitaxial Iron Silicide on Si(111) Studied with X-Ray Diffraction

Abstract: Atomic structures of iron-silicide ultra-thin films epitaxial grown on Si(111) were investigated by x-ray crystaltruncation-rod scattering measurements. Two films, each of them respectively exhibited 1×1 and 2×2 periodicities in ultra high vacuum, were measured with the x-ray diffraction under ambient air. Both of the films showed essentially the same Laue peaks. The Laue peaks directly indicate that both films have the CsCl-type (so-called c-FeSi) structure whose stacking orientation is rotated by 180 • with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Then the method was applied to the analysis of an iron silicide thin film on the Si(111) surface. The result indicated that the iron silicide of Si(111)-2×2-Fe is of CsCl B8-type, consistent with the analysis done by using the least squares fitting [16].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Then the method was applied to the analysis of an iron silicide thin film on the Si(111) surface. The result indicated that the iron silicide of Si(111)-2×2-Fe is of CsCl B8-type, consistent with the analysis done by using the least squares fitting [16].…”
Section: Discussionsupporting
confidence: 85%
“…X-ray intensities were observed along the 00, 10, and 01 rods in atmosphere. Details of the experimental results and analyses using the least squares fitting are described elsewhere [16]. The results support the CsCl-type structure for both samples.…”
Section: Analysis Of Experimental Datasupporting
confidence: 56%
“…2,8 Interest in B2-FeSi increased somewhat recently, however, with the confirmation of antiferromagnetic spin ordering, with potential applications in high-density magnetic data storage and spintronics. 9 While an uncommon phase, a review of the literature does yield several theoretical [10][11][12] and experimental [13][14][15][16] works. These previous studies have reported macroscopic high pressure transitions to the B2 phase at >24 GPa, 14 which is of relevance to the study of geological processes in the Earth's mantle; or thin films and multilayers stabilized epitaxially on carefully prepared surfaces.…”
mentioning
confidence: 99%
“…These previous studies have reported macroscopic high pressure transitions to the B2 phase at >24 GPa, 14 which is of relevance to the study of geological processes in the Earth's mantle; or thin films and multilayers stabilized epitaxially on carefully prepared surfaces. 13,16 The topic of the current letter is the synthesis and characterization of nanodots of B2-FeSi in Si(100) substrates, which have not been reported previously. Samples were prepared in a UHV system (Mantis Deposition Ltd, UK) at ambient temperature, using an Ar þ ion source (MATS) for simultaneous substrate ion etching and iron deposition, similarly to Zhang et al, 18 until a surface coverage of approximately 1 nm of iron was obtained.…”
mentioning
confidence: 99%
“…The results of previous experimental investigations [2][3][4][5][6][7][8][9] showed that the deposition of 2-3 monolayers (ML) of iron onto a Si(111) surface, followed by the annealing of obtained structures at 300-350°C, leads to a change in the surface silicide reconstruction from 1 × 1 to 2 × 2 and the formation of a CsCl type struc ture. The subsequent annealing retains the 2 × 2 peri odicity.…”
mentioning
confidence: 99%